Comprehensive Evaluation of the Expressed CD8+ T Cell Epitope Space Using High-Throughput Epitope Mapping - Lehmann, Paul V.; Suwansaard, Maneewan; Zhang, Ting; Roen, Diana R.; Kirchenbaum, Greg A.; Karulin, Alexey Y.; Lehmann, Alexander; Reche, Pedro A. (Frontiers in Immunology, 2019)
T cell immunity is traditionally assessed through functional recall assays, which detect the consequences of the T cells’ antigen encounter, or via fluorescently labeled multimers that selectively bind peptide-specific T cell receptors. Using either approach, if the wrong antigen or peptide of a complex antigenic system, such as a virus, is used for immune monitoring, either false negative data will be obtained, or the magnitude of the antigen-specific T cell compartment will go largely underestimated. In this work, we show how the selection of the “right” antigen or antigenic peptides is critical for successful T cell immune monitoring against human cytomegalovirus (HCMV). Specifically, we demonstrate that individual HCMV antigens, along with previously reported epitopes, frequently failed to detect CD8+ T cell immunity in test subjects. Through systematic assessment of T cell reactivity against individual nonamer peptides derived from the HCMVpp65 protein, our data clearly establish that i) systematic testing against all potential epitopes encoded by the genome of the antigen of interest is required to reliably detect CD8+ T cell immunity, and ii) genome-wide, large-scale systematic testing of peptides has become feasible through high-throughput ELISPOT-based “brute force” epitope mapping.